Combinatorial Control of Th17 and Th1 Cell Functions by Genetic Variations in Genes Associated With the Interleukin‐23 Signaling Pathway in Spondyloarthritis. Issue 6 (30th May 2013) - Coffre, Maryaline; Roumier, Mathilde; Rybczynska, Magda; Sechet, Emmanuel; Law, Helen K. W.; Gossec, Laure; Dougados, Maxime; Bianchi, Elisabetta; Rogge, Lars
<x xml:space="preserve">Abstract</x> Objective Recent genome‐wide association studies have revealed numerous genetic associations between specific single‐nucleotide polymorphisms (SNPs) and immune‐mediated inflammatory diseases. The current challenge is to identify associations of the genetic variants with effector mechanisms implicated in pathogenesis. This study was undertaken to investigate the link between genetic variation at loci associated with spondyloarthritis (SpA) and the effector function of CD4+ T lymphocyte subsets involved in chronic inflammatory disease. Methods Expression of Th17 and Th1 cytokines and transcription factors was measured in CD4+ T cells isolated from patients with SpA. Correlation analyses were performed to assess potential associations of these expression levels with the patient's genotype at loci genetically linked to SpA. Results The effector functions of Th17 and Th1 cells in patients with SpA were found to be under combinatorial control by multiple SNPs at genes associated with the interleukin‐23 (IL‐23)/Th17 pathway. Patients with SpA carrying risk‐associated alleles of genes in the IL‐23/Th17 pathway expressed the highest levels of genes involved in the differentiation and function of Th17 and Th1 cells, whereas the presence of protective alleles was associated with low‐level expression of these genes. In contrast, variation at loci that were genetically linked to SpA, but not associated with the IL‐23 pathway, did not affect the expression of Th17‐ and Th1‐specific genes, suggesting that these SNPs may contribute to the pathogenesis of SpA through distinct cellular mechanisms. Conclusion These results show that genetic variations at genes associated with the IL‐23 signaling pathway may influence the effector functions of Th17 and Th1 cells in patients with SpA. These findings provide a framework to delineate the mechanisms by which genetic variants contribute to pathology.